ANALISIS VARIABEL KUALITAS PELAYANAN, PROMOSI DAN PRODUK YANG MEMPENGARUHI KEPUTUSAN NASABAH DALAM MENABUNG DI PT BPR ARTHA KANJURUHAN - Intan Dewi Sa’adah; Nur Hidayati; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThis research is conducted by the aim: to know the service quality,promotion, and product variables which influence customers’ decision indepositing at PT BPR ARTHA KANJURUHAN. From the observation, populationused in this research was the customers of PT BPR ARTHA KANJURUHAN whohave been served/ have did transaction on their own account at least in 1 to 5years. Sampling technique of this research was purposive sampling. Based oncriteria, there were 71 respondents as the samples. The research method used wasmultiple linear regressions. Based on research result it can be concluded, that: 1)T result shows that service quality variable gives significant influence on thedecision of depositing. 2) Promotion variable gives significant influence on thedecision of depositing. 3) Product variable gives significant influence on thedecision of depositing. 4) F result shows that service quality, promote, andproduct variables give simultaneous influence on the decision of depositing.Keywords: service quality, promotion, product, and decision of depositing